Hilirisasi Hasil Penelitian Melalui Pemanfaatan Aplikasi Android dalam Pendampingan Gelar Karya Berbasis Pengetahuan Tekstil - Romadhona Chusna Tsani; Mien Zyahratil Umami; Siti Maratus Solikah (Akademi Kesejahteraan Sosial Ibu Kartini Semarang, 2026)
The downstreaming of research outputs was implemented through the use of an Android-based application integrating textile knowledge as a mentoring medium for student exhibitions at SMK Yasemi. This community service program aimed to improve students’ understanding and practical skills in applying textile knowledge to the development of high-quality and sustainable fashion products. A learning-by-doing approach was adopted, encompassing practical simulations, hands-on mentoring, and performance evaluation. The Android application supported textile material selection, alignment between materials and design concepts, and the reinforcement of sustainability principles. The findings demonstrate improvements in students’ textile knowledge, material processing skills, and the overall quality of fashion products presented in the exhibition. These results indicate that the Android-based application, as a form of research downstreaming, is effective in supporting textile knowledge–based exhibition mentoring within vocational education.